Biografi Shaikh Muhammad 'Uthman Al-Mirghani (1208H/1793-4M- 1268H/1852-3M) Dan Sumbangannya Terhadap Pembentukan Tarekat Khatmiyyah - Saari, Che Zarrina (Jurnal Usuluddin, 2001)
This article aims to highlight the founder of the Khatmiyyah Order that spread widely in the Sudan. It tries to gather information about Shaykh Muhammad 'Uthman al-Mirghani who played an important role in organizing and developing the order. As a disciple of a well-known reformist, Shaykh Ahmad bin Idris al-Mirghani is considered a reformist as well. Accordingly, this article also attempts to describe his contribution to sufism.